Efektivitas Isolat Lokal Boyolali sebagai Bakteri Dekomposter - RINANTO, YUDI; FATMAWATI, UMI (Bioedukasi: Jurnal Pendidikan Biologi, 2016)
The aim of this research is to identify the effectiveness of Local Isolate Bacteria from Boyolali (ILB) to decompose organic materials from wasted vegetable and slurry. The result of decomposition were compared to EM4 for control. The laboratory result indicates that Local isolate bacteria from Boyolali were more effective than EM4 to increase N (Nitrogen) content. The ability of Local isolate bacteria from Boyolali was better than EM4 in degrading organic materials of slurry, particularly, towards P (Phosphate). The best concentration of ILB decomposition is 30 %. Liquid fertilizer produced from Slurry with decomposition ILB 30% that applied towards cabbage  increased the weight of cabbage and the length of circumference by 0.5525 gram and 12.67 cm respectively. From the experimental results that it can be concluded that ILB has better capability in decomposing organic material than EM4. ILB has a good potential as decomposter to produces liquid organic fertilizer. Keywords:     Local isolate, decomposter, EM4, Slurry, cabbage